Judicial Intervention to Corporate Governance: Causes and Approaches - Guo , Sheng Xuan (Journal of Law and Governance, 2015)
A corporation is a legal person with group personality created by the law and is considered to have the freedom of autonomy as a subject of private law. A corporation is also considered as shareholders’ tool to pursue profit just like a kite flown by shareholders especially substantial shareholders. A corporation is considered as a contractual combination, a gathering place of stakeholders and constituting a cell of society. A corporation is described as a Utopia. …With different interest claims, subjects such as management, shareholders, directors, creditors, employees and others who coexist in a corporation through the certain formal structure of corporate governance.